Optimization of Human Resources (HR) to Support Blue Economy in Riau Island Province - Afrian Ginanjar; Ade Adriyadi (Journal of Maritime Policy Science, 2024)
Riau Island Province (Kepri) has great potential to support blue economy policies with its territory dominated by oceans (96%) and strategic position on the ASEAN border. Blue economy is an important approach to integrating maritime sectors such as fisheries, marine tourism, renewable energy, and marine technology sustainably. This article aims to analyze the challenges and opportunities in optimizing local human resources (HR) to support the implementation of blue economy policies in Kepri, in order to realize the vision of "Kepri Permata Biru 2045." This study uses a descriptive qualitative method with a phenomenological approach to understand the interaction between government, society, academics, the private sector, and media (Pentahelix Collaboration). Primary and secondary data were obtained through interviews, literature studies, and official documents such as RPJPD and RPJMD. This approach helps explore the dynamics of stakeholders in inclusive and sustainable blue economy governance. The results of the study show that although Kepri has great potential in maritime resources, the implementation of blue economy policies is faced with challenges such as limited inter-regional connectivity, low quality of human resources, and lack of maritime infrastructure. In addition, synergy between actors in collaborative governance is still weak. However, great opportunities can be utilized through investment in marine technology, human resource training, and strengthening the role of local communities